2014
DOI: 10.1515/pjap-2015-0011
|View full text |Cite
|
Sign up to set email alerts
|

Why insight in psychotherapy does not always lead to behaviour change?

Abstract: The purpose of this review was to come closer to answering the question why insight gained in psychotherapy does not necessarily lead to a change in patient’s behaviour. The review of literature on the subject of insight allowed us to distinguish two types of insight: “more intellectual than emotional” (I-e) and “more emotional than intellectual” (E-i). In addition, we differentiated E-i insight with a component of negative emotions (aversive) and with a component of positive emotions (corrective). We assumed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…That psychological insight is strongly related to decreases in depression and anxiety is perhaps not surprising given the history of insight-oriented therapies (Connolly Gibbons et al, 2007), but it has also been questioned whether gaining insight is sufficient in and of itself to produce lasting changes in behavior or mental health functioning (Kuncewicz, Lachowicz-Tabaczek, and Zaluski, 2014;Leichsenring et al, 2006). To this point, our models also showed that psychological insight was predictive of change when accounting for the correlation between insight and mystical experiences.…”
Section: Discussionmentioning
confidence: 50%
“…That psychological insight is strongly related to decreases in depression and anxiety is perhaps not surprising given the history of insight-oriented therapies (Connolly Gibbons et al, 2007), but it has also been questioned whether gaining insight is sufficient in and of itself to produce lasting changes in behavior or mental health functioning (Kuncewicz, Lachowicz-Tabaczek, and Zaluski, 2014;Leichsenring et al, 2006). To this point, our models also showed that psychological insight was predictive of change when accounting for the correlation between insight and mystical experiences.…”
Section: Discussionmentioning
confidence: 50%
“…Third, neuroscience suggests that conscious insight is not needed for change (Kuncewicz, Lachowicz, & Zaluski, 2014). Lyons-Ruth (1998) found that what clients recall about their therapeutic experience is the relationship with the therapist and not the specific techniques used.…”
Section: Resultsmentioning
confidence: 99%
“…A broader, transtheoretical definition of interpretation is “a statement that goes beyond what the patient has overtly stated or recognized and gives a new meaning, reason, or explanation for behaviors, thoughts, or feelings so that the patient can see problems in a new way” (Hill, 2020, p. 255). Awareness of such maladaptive patterns, when it is not only intellectual but also emotionally involved, is expected to raise insight, which in turn is expected to result in cognitive and behavioral change, symptom reduction, and an increase in well-being (Kuncewicz et al, 2014).…”
Section: Definitions and Clinical Descriptionmentioning
confidence: 99%